Bevacizumab combined with first-line carboplatin and paclitaxel for metastatic/recurrent/persistent cervical cancer: primary results from the global single-arm phase II CECILIA study. (1st November 2019) - Colombo, N; Dreosti, L; McCormack, M; Nogueira-Rodrigues, A; Scambia, G; Roszak, A; Donica, M; Ulker, B; González-Martín, A; Redondo, A
Abstract : Introduction/Background: In the phase III GOG240 trial, combining bevacizumab with paclitaxel and cisplatin/topotecan for advanced cervical cancer significantly improved overall and progression-free survival. The single-arm phase II CECILIA study (NCT02467907 ) evaluated bevacizumab with a more widely used chemotherapy backbone. Methodology: The primary objective was to determine the safety of bevacizumab/carboplatin/paclitaxel for advanced cervical cancer, defined by the frequency and severity of gastrointestinal (GI) perforation/fistula, GI-vaginal fistula and genitourinary (GU) fistula. Eligible patients had metastatic/recurrent/persistent cervical cancer not amenable to curative surgery and/or radiotherapy. Patients with ongoing bladder/rectal involvement, prior cobalt radiotherapy, history of fistula/GI perforation, or bowel resection ≤6 weeks or chemoradiation ≤3 months before starting bevacizumab were excluded. Patients received bevacizumab 15 mg/kg, paclitaxel 175 mg/m 2 and carboplatin AUC5 q3w until disease progression, unacceptable toxicity or consent withdrawal. If any drug was stopped for toxicity, the remaining drug(s) could be continued alone. Results: Between July 2015 and December 2016, 150 patients began treatment. Baseline characteristics at study entry were: 20%/53%/27% with persistent/recurrent/de novo metastatic disease; 71%/58%/59% with prior radiotherapy/chemoradiation/platinum. Median treatment duration was 6.7 (range <1–39) months for bevacizumab and 3.9 (range 0–14.6) months for chemotherapy; 57% of patients received single-agent bevacizumab after discontinuing chemotherapy. Table 1 summarises primary endpoint results. In 17 patients with fistula/perforation events, median time to onset was 3.8 (range 0.3–12.4) months. Grade 3/4 adverse events occurred in 73% of patients, most commonly neutropenia/neutrophil count decreased (25%), anaemia (19%) and hypertension (14%). Grade 5 adverse events occurred in 3%. Figure 1 shows progression-free and overall survival. The objective response rate was 61% (95% CI 52–69%), including complete responses in 14% (9–21%). Conclusion: Bevacizumab can be combined with carboplatin/paclitaxel chemotherapy in the cervical cancer population treated in CECILIA. The fistula/GI perforation incidence is in line with GOG240. Efficacy results are encouraging. Disclosure: Nicoletta Colombo:advisor/consultant for Roche, PharmaMar, AstraZeneca, Tesaro, Clovis, Pfizer, MSD, BIOCAD, Takeda, Lilly; travel/accommodation expenses from Roche, PharmaMar, Tesaro. Lydia Dreosti: honoraria for advisory/consultancy roles from Eli Lilly, MSD; travel/accommodation expenses from Janssen, Merck. Mary McCormack: honoraria from AstraZeneca, Roche. Angélica Nogueira-Rodrigues: honoraria for advisory boards/consultancy from Roche, AstraZeneca, MSD; research funding to institution from Roche, MSD. Giovanni Scambia, Andrzej Roszak: no conflict of interest. Margarita Donica: employee of F Hoffmann-La Roche; shares in Novartis. Bulent Ulker: contracted to work on behalf of F Hoffmann-La Roche. Antonio González-Martín: advisory boards for Roche, AstraZeneca, Tesaro, Clovis, Pfizer, ImmunoGen, PharmaMar, MSD, Genmad; speaker bureau for Roche, PharmaMar, Tesaro, AstraZeneca; research funding to institution from Roche, Tesaro. Andrés Redondo: honoraria from AstraZeneca, Roche Farma, Tesaro, Clovis, Pharmamar, Lilly, Eisai; advisory boards for AstraZeneca, Roche Farma, Tesaro, Clovis, Pharmamar, Lilly; travel/accommodation from AstraZeneca, Tesaro, PharmaMar, Roche Farma; research funding to institution from Eisai, PharmaMar, Roche Farma.